Advancing BRAC Graduates (ABG) – the future champion programme, BRAC Education Programme (BEP) - Parvez, Herana (BRAC University, 2017)
This internship report is submitted in partial fulfillment of the requirements for the degree of Masters in Development Management and Practice, 2016.